Community-based study on elderly CKD subjects and the associated risk factors. (25th November 2016) - Huang, Yan-Ping; Zheng, Tao; Zhang, Dan-Huan; Chen, Ling-Yun; Mao, Pei-Jv
Abstract: Objective: To investigate the prevalence and risk factors for chronic kidney disease (CKD) among community elderly population in Shanghai, China, in order to provide early diagnosis and treatment of CKD, and improve the quality of life for elderly people. Methods: In all, 24, 886 residents (≥65 years old) were selected from community population in Changning District of Shanghai, China in 2014. They were interviewed and tested for reduced renal function estimated GFR by CKD-EPI equation. The associations among demographic characteristics, healthy characteristics (e.g., cardiovascular disease and hypertension), and indicators of kidney damage were examined. Results: Approximately, 16.4% of the participants were CKD. The average of them was 74.9 ± 7.0 years old. Females had a significantly higher prevalence of CKD than males (17.6% vs. 14.9%). CKD patients were present in higher prevalence of female, hyperuricemia (29.6% vs. 18.7%), hypertension (45.1% vs. 40.3%), and cardiovascular disease (23.2% vs. 18.7%) than that of non-CKD population. CKD patients were present in lower prevalence of drinking than that of non-CKD population. The prevalence of CKD in female is 2.002 times than that of male. The prevalence of CKD increased 1.048 times with the age of each increase in 1 year old. The risk factors for CKD are age, female, hyperuricemia, cardiovascular disease, hypertension, hypercholesterolemia, and smoking. Conclusions: The prevalence of CKD is high in the elderly population than that of adult CKD in Shanghai. The most risk factors for elderly CKD patients are similar to the adult population. But hypercholesterolemia as a risk fact of elderly CKD is different from adult CKD.